Service-led growth and the balance of payments constraint in India: An unsustainable strategy - Suranjana Nabar-Bhaduri; Matías Vernengo (The University of Utah, Department of Economics, 2012)
India has been an exemplary case of economic growth, lionized in the international press as one of the emerging market economies that will take over the world economy in the current century. The Indian services revolution is often cited as an example of an alternative development strategy under which the process of growth is services-led, as against the traditional manufacturing-led paradigm that has historically been the case. This paper suggests that the Indian development strategy actually looks eerily similar to the Central American and Mexican patterns of integration into the world economy, which are highly dependent on the exports of people, directly through migration, and indirectly through low wages in particular sectors ('maquilas' in the Americas, the call centers in India), even if the growth rates in India have been considerably higher than in those Latin American regions.
Keywords: O11; O14; O53; 330; Economic Development; Service Sector; India